WASH for Human Development : Can Scaling Up Water Supply, Sanitation, and Hygiene Interventions Help Children Grow in Tanzania? - World Bank Group (World Bank, Washington, DC, 2017)
In Tanzania, chronic undernutrition is at 35 percent among children under five. This makes the country home to the third highest population of children with chronic undernutrition in Sub-Saharan Africa, just after Ethiopia and the Democratic Republic of Congo. This brief provides an overview of the trends in undernutrition, as indicated by stunted growth, over time and by subgroups of gender, age in months, rurality, geography, and poverty. It also provides a geo-spatial stunting map which shows 1km x 1km pixel-level estimations of stunting rates. Using the UNICEF Synergies Approach (1990) and drawing on existing scientific literature, the brief then outlines the theory behind different pathways to chronic undernutrition through inadequate food, care, environment, and health services. Further econometric analysis has been conducted on the DHS 2016 data using Shapley decomposition, to identify the relative contributions of various determinants including water supply, sanitation, and hygiene (WASH) variables in determining stunting rates, and hence chronic undernutrition in the Tanzania. The relative contributions of other factors such as poverty, the child’s characteristics, mother’s characteristics and location are also highlighted. Finally, it provides operational and policy implications along the lines of multisectoral and nutrition-sensitive approaches for intervention design to reduce stunting in Tanzania.